ICT in process safety management - Hooi, Y.K. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper analyzes the impact of Information Communications Technology (ICT) in process safety management of Highly Hazardous Chemicals. Although computer systems have been used in control systems, much work is yet to be done to address safety at high level. The authors conducted extensive cross-field literature study and field study to verify findings. Three challenges for ICT in process safety are integration of process safety subsystems and activities; quality assurance; and propagation of safety information. Discussion begins with concepts of process safety, safety controls, safety tools and safety management. The following sections discuss software categories for process safety and analyses ICT impacts. The contribution of this paper is general picture of ICT landscape in process safety environment and fresh leads for ICT to optimize plant safety. Â© 2014 IEEE.